Pengaruh Kepemimpinan Visioner Kepala Sekolah dan Motivasi Kerja terhadap Kepuasan Kerja Guru di SMAN6 Muaro Jambi - Jazilatul Atiyyah; Mulyadi Mulyadi; Linardo Pratama (Muróbbî: Jurnal Ilmu Pendidikan, 2025)
This study aims to determine the effect of the school principal’s visionary leadership and work motivation on teacher’s job satisfaction, as well as to examine the effect of the school principal’s visionary leadership on work motivation at SMAN 6 Muaro Jambi. The research employs a quantitative approach with data analysis techniques Structural Equation Modeling (SEM) with the assistance of SmartPLS 3.0 software. This study is a survey research. The population consists of 40 teachers at SMAN 6 Muaro Jambi, and the sample includes the entire population of 40 teachers. The study results indicate that: (1) There is a positive but not significant effect of the school principal’s visionary leadership on teacher’s job satisfaction, with p-value > 0.05, specifically 0.513, a T-statistic value of 0.564, and a path coefficient of 0.155. (2) There is a positive and significant effect of work motivation on teacher’s job satisfaction, with p-value < 0.05, specifically 0.000, a T-statistic value of 7.523, and path coefficient of 0.777. (3) There is a positive and significant effect of the school principal’s visionary leadership on work motivation, with p-value < 0.05, specifically 0.002, a T-statistic value of 3.121, and a path coefficient of 0.631.